(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2019)
Massimo Alvisi, artistic director of the Rome Auditorium construction site for Renzo Piano’s office, recomposes in a short story-interview the significant events of the construction of the work, dialoguing on the future of the urban area of Flaminio.